Integration of antennas with sun‐tracking solar panels. Issue 15 (1st July 2016) - Narbudowicz, A.; O'Conchubhair, O.; Ammann, M.J.; Heberling, D.
Abstract : A low‐cost solution for antennas integrated into solar cells, allowing their implementation in solar tracking installations is proposed. The proposed passive device autonomously adjusts the phase shift of a two‐element array proportional to the panel rotation. Consequently, the main beam is steered to compensate for panel rotation and maintain a radio link. The proposed device operates for a rotation of ±45° with an amplitude variation of ≤0.4 dB at 2.51 GHz.